Finding real world software vulnerabilities using ChatGPT - Wong, Sean Chun Foh (Nanyang Technological University, 2024)
The rapid integration of artificial intelligence (AI) into cybersecurity has introduced revolutionary tools for vulnerability assessments, where AI's pattern recognition capabilities and natural language processing can potentially help in cybersecurity detection and remediation strategies. This paper explores the potential between AI and cybersecurity through the lens of a YAML-based ChatGPT agent named MasterEngineer, devised to automate the highlighting of software vulnerabilities and offer learning insights into their nature and resolution of the vulnerable code. The research is directed towards examining the effectiveness of MasterEngineer in assessing source code vulnerabilities across various languages and decompiled C code, juxtaposed with traditional static and dynamic analysis tools.